Assessment of Inflammatory Biomarkers, Total IgE levels, SNOT-22 scores in Allergic Rhinitis patients - Yazıcı, Dr. Demet (ENT Updates, 2019)
Objective: The aim of this study is to assess neutrophil-lymphocyte ratio (NLR), mean platelet volume (MPV), platelet-lymphocyte ratio (PLR) and eosinophil-lymphocyte ratio (ELR) of allergic rhinitis patients and compare our findings with healthy controls. We also analyzed the effect of severity of allergic rhinitis on hematological parameters and total IgE levels of the patients. Methods: A total of forty-six patients diagnosed having allergic rhinitis according to Allergic Rhinitis and its Impact on Asthma (ARIA) criteria and forty-six healthy, age and sex-matched subjects were included in this study. The clinical records of the patients were retrospectively analyzed and age, gender, skin prick test results, complete blood counts, total IgE levels and Sino-Nasal Outcome Test (SNOT) 22 scores were recorded for assessment of neutrophil-lymphocyte ratio (NLR), mean platelet volume (MPV), platelet-lymphocyte ratio (PLR) and eosinophil-lymphocyte ratio (ELR) of the patients. Results: Eosinophil count, eosinophil percentage and ELR value of the study group were significantly higher than the control group (p=0.001, p=0.001, p=0.001, respectively). The cut-off value for ELR was ≥0.105 (sensitivity=0.61, specificity=0.76, AUC=0.703). Total IgE levels of patients with positive skin prick test were significantly higher than patients with negative skin prick test (p=0.019). The cutoff value for total IgE was ≥63 IU/mL (sensitivity=0.59, specificity=0.74, AUC=0.706). Conclusion: ELR is a valuable marker for predicting allergic rhinitis. However, it does not correlate with the severity of the disease. Total IgE levels increase in patients with positive skin prick tests. Also, total IgE level does not correlate with the severity of allergic rhinitis.